FORSA Program: From Welfare To Workfare - Elshabrawy, Atef (2020)
“IFPRI Egypt Webinars” is a special edition of the IFPRI Egypt Seminar Series funded by USAID. This webinar took place under the title of “COVID-19 and social protection: from effective crisis protection to self-reliance”